Business Plan Cofee Shop Students with SWOT Analysis - Fajri, Chotamul; Sairin; Suworo (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The purpose of this study is to analyze the Business plan of the Santri Coffee Shop using the SWOT Analysis approach. And to find out the benefits of the existence of the Santri Coffee Shop in the Alwafi Boarding School environment. This study uses a qualitative method by conducting interviews, observations and documentation at the research location at the Santri Coffee Shop Alwafi Islamic Boarding School Pengasinan Depok. The analysis used SWOT Analysis, so that it can be used as an alternative to compile a Business Plan in business development at the Santri Coffee Shop Alwafi Islamic Boarding School Pengasinan Depok.Business in the current era is included in the more modern category combining all categories and places of business. For the culinary sector, in addition to high-end restaurants, there are also small-scale ones such as cafes and stalls. Seeing the opportunities and behavior of society in general, makes business actors engaged in the food and beverage sector glance at the coffee shop business, which focuses on the coffee sector by prioritizing a comfortable and homey atmosphere, both for workers and customers. With the current conditions, the presence of a coffee shop is considered the most appropriate for the lifestyle of urban communities. No exception for the santri environment, such as the one at the Al Wafi Islamic Boarding School Pengasinan Depok Islamic Boarding School. With the presence of Santripreneurs who are part of independent learning, the Coffee Shop is present in addition to teaching santri to be entrepreneurs, it is also a business opportunity that is usually a gathering place in the city, arranged according to the santri atmosphere by presenting a healthy coffee sensation in one of the canteen outlets of the Islamic boarding school.